Organocatalytic Asymmetric Methodologies towards the Synthesis of Atropisomeric N-Heterocycles - Corti, Vasco; Bertuzzi, Giulio (Synthesis, 2020)
A perspective on the literature dealing with the organocatalytic asymmetric preparation of axially chiral N-heterocycles is provided. A particular focus is devoted to rationalize the synthetic strategies employed in each case. Moreover, specific classes of organocatalysts are shown to stand out as privileged motives for the stereoselective preparation of such synthetically challenging molecular architectures. Finally, an overview of the main trends in the field is given.1 Introduction2 Five-Membered Rings2.1 Arylation2.2 Dynamic Kinetic Resolution2.3 Ring Construction2.4 Central-to-Axial Chirality Conversion and Chirality Transfer2.5 Desymmetrization3 Six-Membered Rings3.1 Desymmetrization3.2 (Dynamic) Kinetic Resolution3.3 Ring Construction3.4 Central-to-Axial Chirality Conversion4 Conclusion
Keywords: heterocycles; atropisomerism; organocatalysis; indole; pyrrole; pyridine; quinoline